What Influences Successful Communication? An Examination of Cognitive Load and Individual Differences. Issue 10 (25th November 2020) - Navarro, Ester; Macnamara, Brooke N.; Glucksberg, Sam; Conway, Andrew R. A.
ABSTRACT: The underlying cognitive mechanisms explaining why speakers sometimes make communication errors are not well understood. Some scholars have theorized that audience design engages automatic processes when a listener is present; others argue that it relies on effortful resources, even if a listener is present. We hypothesized that working memory is engaged during communicative audience design and that the extent to which working memory is engaged relies on individual differences in cognitive abilities and concurrent amount of resources available. In Experiment 1, participants completed a referential task under high, low, or no cognitive load with a present listener whose perspective differed from the speaker's. Speakers made few referential errors under no and low load, but errors increased when cognitive load was highest. In Experiment 2, the listener was absent. Speakers made few referential errors under no and low load, but errors increased when cognitive load was highest, suggesting that audience design is still effortful under high cognitive load, both when the listener was present and when the listener was absent. Experiment 3 tested whether cognitive abilities predicted communication performance. Participants with higher fluid intelligence and working memory capacity made fewer communication errors. Our findings suggest that communication relies on available cognitive resources, and therefore errors occur as a function of factors like cognitive load and individual differences.